"Craziness" and "visions": experiences after a stroke. Issue 6613 (19th December 1987) - Wender, D
Abstract : For a stroke victim there may be at least three types of strange occurrences: incorrect saying, seeing, and thinking. To the patient only the third seems to be "crazy". After a stroke (left hemisphere), which mainly produced serious aphasia, I (the patient) felt crazy two or three times when someone said something I expected him to say. On the other hand, my initial aphasic "gibberish speech" and an occasional false vision did not seem crazy. In my case the vision is always a car or a child, seen on my extreme right, where I am otherwise blind from the stroke. I am always driving when it happens; in recent years this phenomenon occurs when I am tired or tense, or the light is poor. These rapid visions do not seem insane but merely physical problems in my eyes, much like ordinary people's dreams.